2005
DOI: 10.1093/pcp/pci050
|View full text |Cite
|
Sign up to set email alerts
|

Similar Regulation Patterns of Choline Monooxygenase, Phosphoethanolamine N-Methyltransferase and S-Adenosyl-l-Methionine Synthetase in Leaves of the Halophyte Atriplex nummularia L.

Abstract: Glycinebetaine (betaine) highly accumulates as a compatible solute in certain plants and has been considered to play a role in the protection from salt stress. The betaine biosynthesis pathway of betaine-accumulating plants involves choline monooxygenase (CMO) as the key enzyme and phosphoethanolamine N-methyltransferase (PEAMT), which require S-adenosyl-L-methionine (SAM) as a methyl donor. SAM is synthesized by SAM synthetase (SAMS), and is needed not only for betaine synthesis but also for the synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 56 publications
5
57
0
Order By: Relevance
“…Transcripts for (or specific activities of) these betainerelated enzymes, with the exception of MS, are reported to be upregulated by salt stress in chenopod leaves (McCue and Hanson 1992;Russell et al 1998;Rontein et al 2001;Weretilnyk et al 2001;Tabuchi et al 2005). We previously reported that the regulation pattern of CMO transcripts resembles that of PEAMT and SAMSs in A. nummularia leaves under salt stress, after relief from salt stress and on a diurnal rhythm (Tabuchi et al 2005).…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Transcripts for (or specific activities of) these betainerelated enzymes, with the exception of MS, are reported to be upregulated by salt stress in chenopod leaves (McCue and Hanson 1992;Russell et al 1998;Rontein et al 2001;Weretilnyk et al 2001;Tabuchi et al 2005). We previously reported that the regulation pattern of CMO transcripts resembles that of PEAMT and SAMSs in A. nummularia leaves under salt stress, after relief from salt stress and on a diurnal rhythm (Tabuchi et al 2005).…”
mentioning
confidence: 92%
“…We previously reported that the regulation pattern of CMO transcripts resembles that of PEAMT and SAMSs in A. nummularia leaves under salt stress, after relief from salt stress and on a diurnal rhythm (Tabuchi et al 2005). In order to further examine the co-regulation of betaine-related genes in chenopods, we compared the Plant Biotechnology 23, 317-320 (2006) Transcriptional response of glycinebetaine-related genes to salt stress and light in leaf beet patterns of transcript expression in a broader range of betaine-related genes in B. vulgaris, which is one of the most important agricultural chenopod species.…”
mentioning
confidence: 94%
See 3 more Smart Citations